Pollutant Dispersion in Built Environment - Ming, Tingzhen; Peng, Chong; Gong, Tingrui; Li, Zhengtong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book discusses energy transfer, fluid flow and pollution in built environments. It provides a comprehensive overview of the highly detailed fundamental theories as well as the technologies used and the application of heat and mass transfer and fluid flow in built environments, with a focus on the mathematical models and computational and experimental methods. It is a valuable resource for researchers in the fields of buildings and environment, heat transfer and global warming.
Fluid flow and heat transfer models in built environment -- Heat transfer and pollutant dispersion in built environment -- Energy generation and pollutant absorption in a novel building. .
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Energy policy; Energy and state; Environmental sciences -- Mathematics; Continuum mechanics; Pollution; Engineering Thermodynamics, Heat and Mass Transfer; Energy Policy, Economics and Management; Mathematical Applications in Environmental Science; Continuum Mechanics; Pollution